PENGARUH TELENURSING TERHADAP KEPUASAN PELAYANAN INFORMASI PADA PASIEN YANG TELAH DI RAWAT DI RUANG PU 3 RS. A TANGERANG - Atika Mutia; Jaenudin; Nunik Yuli. A; M. Martono Diel (Nusantara Hasana Journal, 2023)
Background: Innovation in the provision of telenursing nursing care allows its application in home care services, the scope of nursing services is wider and more equitable, can be utilized in the field of nursing education, and can increase nurse and patient satisfaction with the nursing services provided and the quality of care services more increasing. Objective: To know the effect of telenursing seen from the information service satisfaction obtained on patients who have been treated in Public Works Room 3, Hospital A Tangerang. Methods: This study used the Non-Parametric Mann-Whitney test, with a data scale that was not normally distributed. The subjects in this study were 50 patients who had been hospitalized in Public Works Unit 3 RS.A. This research method uses total sampling. Results: From the results of the Mann-Whitney test, it was obtained a P-value of 0.000 or <0.05, so it can be concluded that there is an effect of telenursing on satisfaction with information services in patients who have been treated in PU room 3 RS.A. then Ha is accepted and Ho is rejected.